The kite runner - Horberg, William; Parkes, Walter F.; Yeldham, Rebecca; Walsh, E. Bennett; Benioff, David; Forster, Marc, 1969-; Abdalla, Khalid; Ershadi, Homayoun; Toub, Shaun; Leoni, Atossa; Taghmaoui, Said; Ebrahimi, Zekiria; et al. (Paramount Home Entertainment, 2008)
In a divided country on the verge of war, two childhood friends, Amir and Hassan, are about to be torn apart forever. It's a glorious afternoon in Kabul and the skies are bursting with the exhilarating joy of a kite-fighting tournament. But in the aftermath of the day's victory, one boy's fearful act of betrayal will mark their lives forever and set in motion an epic quest for redemption. Now, after twenty years of living in America, Amir returns to a perilous Afghanistan under the Taliban's iron-fisted rule to face the secrets that still haunt him and take one last daring chance to set things right.